The judiciary under threat - Batalla, Eric Vincent C. (Animo Repository, 2018)
Despite increased powers granted by the 1987 constitution and recent institutional reforms, judicial performance leaves much to be desired. International indices suggest that rule of law and judicial independence as well as access to justice remain important challenges for the judiciary. Its effectiveness is further hampered by continuing political susceptibility and severe capacity constraints. The impeachment of the Chief Justice of the Supreme Court during the Benigno S. Aquino, III administration represents a highpoint to an institution’s political susceptibility. Nevertheless, the judiciary remains an important political institution that resolves political and policy conflicts in the country. © 2018 selection and editorial matter, Mark R. Thompson and Eric Vincent C. Batalla; individual chapters, the contributors.